Biogas production by codigestion of fruit and vegetable wastes: organic loading rate (OLR) effect study - Mel, Maizirwan; Avicenna, Avicenna; Mohd Rodzi, Muhammad Zulkhairy; Ihsan, Sany Izan; Ismail, Ahmad Faris; Yaacob , Sharifah (2013)
In this study, experiments were conducted to investigate the production of biogas from co-digestion of fruit and vegetable wastes using anaerobic process. The complete-mix, pilot-scale digester with working volume of 2100 litter was used. The experimental protocol was defined to examine the effect of the change in the organic loading rate (OLR) on the quality of the biogas production and to report on its steady-state performance. The digester was operated at different organic feeding rates of 1.5, 3 and 4.5 kg VS/ (m3.d). The biogas had produced methane composition of 48 - 62% and biogas production rates of 0.1-0.5 m3 biogas/(kg VS input). The reactor showed stable performance with highest methane with VS reduction during loading rate of 1.5 kg VS/(m3.d). As the organic loading rate was increased, the VS degradation and biogas yield tend to decreased. Based on data obtained, OLR of 1.5 kg VS/(m3.d) is suggested as design criteria with the higher methane production rate and successful implementation of anaerobic digestion as the method of waste treatment leads to the utilization of renewable energy resources.